Cover Feature: Accessing Cationic α‐Silylated and α‐Germylated Phosphorus Ylides (Chem. Eur. J. 1/2022). Issue 1 (18th December 2021) - Krämer, Felix; Radius, Michael; Hinz, Alexander; Dilanas, Melina E. A.; Breher, Frank
Abstract : Competition for the lone pair : Our paper describes efforts to access cationic α‐silylated (and α‐germylated) phosphorus ylides of the general formula [R3 PC(R)SiR2 ] + . One inherent feature of these molecules is that the silyl and phosphonyl entities compete for the lone pair of electrons. The ambivalent nature of the possible resonance structures is reflected in the coloured segmentation of the cover feature. The two "competitors" are illustrated as sportspersons, and both resonance structures are represented depending on where the ball of positive change is. More information can be found in the Research Article by F. Breher et al. (DOI: 10.1002/chem.202103974 ).